2023
DOI: 10.1039/d2an01953a
|View full text |Cite
|
Sign up to set email alerts
|

Solvent effects of N,N-dimethylformamide and methanol on mass spectrometry imaging by tapping-mode scanning probe electrospray ionization

Abstract: Mass spectrometry imaging (MSI) is an effective technique for visualizing the distribution of lipids in tissues. The direct extraction-ionization methods using minute volumes of solvent for local components have the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…We previously reported that a mixture of DMF and MeOH is appropriate for imaging lipids in mouse brain tissues. 23 Thus, we studied the A/P–D curves using a DMF/MeOH mixture. t-SPESI allows us to change the solvent composition, which can improve the selectivity and/or efficiency of the extraction–ionization of biological molecules.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We previously reported that a mixture of DMF and MeOH is appropriate for imaging lipids in mouse brain tissues. 23 Thus, we studied the A/P–D curves using a DMF/MeOH mixture. t-SPESI allows us to change the solvent composition, which can improve the selectivity and/or efficiency of the extraction–ionization of biological molecules.…”
Section: Resultsmentioning
confidence: 99%
“…A previously reported t-SPESI system was used. 23 A capillary probe was oscillated using a piezo actuator (PMF-3030, NTK Ceramic, Japan). The PMF-3030 is a small piezo actuator with a diameter of 7.3 mm and length of 17.2 mm, and is capable of providing a maximum displacement of 10 μm.…”
Section: T-spesi Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Although DMF solvent mixtures yield spectra of relatively comparable quality, they favor low molecular mass compounds’ detection [ 4 ]. Moreover, due to its higher surface tension and boiling point compared to MeOH’s, DMF mixtures tend to produce larger spot sizes resulting in enlarged extraction areas and lower spatial image resolution, an effect that could be further intensified by the temperature functionality of the DESI XS system and HTL [ 4 , 13 , 21 ]. In this study case, we report a workflow that utilizes a single tissue section to obtain high molecular and phenotypical information, through multimodal imaging techniques, suitable for AI-enabled image analysis.…”
Section: Introductionmentioning
confidence: 99%